Improving the Mathematical Comprehension and Learning Independency through Discovery Learning Model on Trigonometry for High School Students - Nelliani Nelliani; Anwar Anwar; Anizar Ahmad (Proceedings of AICS - Social Sciences, 2018)
The background study of this research was based on the lack of mathematical understanding and students’ learning independency of Class X at one of the senior high schools in Aceh Besar. The test results on the trigonometry subject showed that only 3 out of 10 students (30%) passed the minimum score. This condition was also found during the observation of student activities in their learning process. Students tended to rely on teachers and friends to cope with the problems, such as lack of initiative, have poor learning management and easy to feel discouraged. The main objectives of this research were (1) to improve students’ mathematical comprehension, and (2) to improve students’ learning independency through discovery learning model on the trigonometry subject. This is a classroom action research. The subjects of this study were ten students at Class X of science class. The research instruments consisted of a set of mathematical comprehension test and students independent learning questionnaire. The technique of data collection used was a qualitative approach, and the collected data was described in descriptive form. The results show that there was an improvement of the learning process through the discovery of learning model, based on the mathematical comprehension test results (from 68.3% in cycle I to 71.7% in cycle II), and the improvement of student’s independent learning (from 42.2% in cycle I to 47.1% in cycle II). Therefore, Discovery learning model effectively improves students' understanding ability, encourage student-learning independency and enlarge students’ mathematical comprehension.Keywords: mathematical comprehension, learning independence, discovery learning.